Analisis Hubungan Antara Struktur Tanah dan Produksi Biomassa Tanaman - Zebua, Charles Septiawan; Harefa, Wendi Warisman (Jurnal Ilmu Pertanian dan Perikanan, 2024)
This research aims to analyze the relationship between soil structure and plant biomass production. Soil structure is an important factor that influences plant growth through its influence on aeration, drainage and nutrient availability. In this research, soil physical parameters were measured, such as density, porosity and aggregate size, as well as observations of plant biomass production in various types of soil. The analysis results show that soil with good structure, characterized by high porosity and low density, tends to produce higher biomass. Additionally, a significant positive relationship was found between soil aggregate size and the volume of biomass produced. These findings emphasize the importance of managing soil structure to increase crop productivity, as well as providing insights for sustainable agricultural practices. It is hoped that this research can become a reference for farmers and land managers in efforts to increase agricultural yields through improving soil structure.